Integral Assessment of Inactive Rail Lines JSC "Russian Railways" as the Basis for Effective and Reasonable Use of their Infrastructure in the Regional Transport Network - Sirina, Nina Fridrikhovna; Yushkov, Mikhail Evgenevich; Galkin, Aleksandr Gennadevich (Economy of Regions, 2015)
In the present paper, we consider the organizational and economic mechanism of relations between the participants of the transportation process for the efficient use of infrastructure of inactive rail lines JSC “ Russian Railways “ (the lines). The purpose of the work is to develop tools to support the cost-effective use of infrastructure lines. One of the productive directions in solving the problem of inefficient use of infrastructure lines in modern conditions of the restructuring of “Russian Railways” is an integral criterion of the lines based on the theory of active systems. Using a model of relations between members of the transportation process will enable to ground the expediency of the use of infrastructure lines and consolidate joint efforts in the region, businesses, and JSC “Russian Railways” for the goal.